2012
DOI: 10.1099/mic.0.062109-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus adherence to Candida albicans hyphae is mediated by the hyphal adhesin Als3p

Abstract: The bacterium Staphylococcus (St.) aureus and the opportunistic fungus Candida albicans are currently among the leading nosocomial pathogens, often co-infecting critically ill patients, with high morbidity and mortality. Previous investigations have demonstrated preferential adherence of St. aureus to C. albicans hyphae during mixed biofilm growth. In this study, we aimed to characterize the mechanism behind this observed interaction. C. albicans adhesin-deficient mutant strains were screened by microscopy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
189
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(205 citation statements)
references
References 44 publications
9
189
0
4
Order By: Relevance
“…Although C. albicans is commonly encountered as a commensal in healthy individuals, this opportunistic pathogen is capable of invading virtually any site of the human host, from superficial sites to deep tissues and organs. C. albicans and S. aureus are frequent colonizers of human mucosal surfaces; using confocal fluorescent and atomic force microscopy, our previous in vitro studies revealed a unique mixed biofilm architecture wherein S. aureus associated closely with the hyphae (34,52). However, in order to investigate the clinical implications of this interaction during cocolonization of host mucosal tissue, a suitable animal model is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. albicans is commonly encountered as a commensal in healthy individuals, this opportunistic pathogen is capable of invading virtually any site of the human host, from superficial sites to deep tissues and organs. C. albicans and S. aureus are frequent colonizers of human mucosal surfaces; using confocal fluorescent and atomic force microscopy, our previous in vitro studies revealed a unique mixed biofilm architecture wherein S. aureus associated closely with the hyphae (34,52). However, in order to investigate the clinical implications of this interaction during cocolonization of host mucosal tissue, a suitable animal model is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro studies have demonstrated that S. aureus exhibits high affinity to the C. albicans hyphae as these species coexist in biofilm and identified the C. albicans hyphal specific adhesin Als3p to be involved in the coadherence process (34,35). Further, our previous in vivo studies have indicated that the interaction of these species may carry important clinical implications (36,37).…”
mentioning
confidence: 99%
“…Genetic manipulation of this adhesin has been shown to reduce bacterial binding to hyphal filaments of C. albicans, reducing the invasive capacity of this relationship [55]. The role of this phenotype has been shown in several bacterial pathogens including Staphylococcus aureus, Streptococcus gordonii, and Streptococcus agalactiae [56][57][58]. Interestingly, when the Δals3 strain was grown with S. mutans, no reduction was observed in mixed species biofilm formation, suggestive of a different mechanism of interaction [59].…”
Section: Caries: Slimy Residentsmentioning
confidence: 99%
“…Approximately one-fourth of all C. albicans bloodstream infections appear to be polymicrobial (33), and coinfection with C. albicans and the important bacterial pathogen S. aureus in mice is synergistic to increase mortality (36). C. albicans and S. aureus were shown to interact directly by forming a mixed biofilm (34) that depended to a considerable extent on the C. albicans Als3 cell wall protein (37). Importantly, mixed biofilm formation with C. albicans enhanced the resistance of S. aureus to vancomycin (35), which, like the more recent antibiotic daptomycin, is being used as a reserve-type antibiotic to combat multiresistant Gram-positive bacterial pathogens, including Staphylococcus, Enterococcus, and Corynebacterium species.…”
Section: Discussionmentioning
confidence: 99%